Revitalizing the Value of Religious Moderation in Realizing Peaceful and Inclusive Education to Prevent Extremist Behavior Among Students - Khadavi, Jadid; Ahmad Fuad Abdul Baqi; Md Noor Hussin (Journal of Islamic Civilization, 2025)
This study aims to examine and analyze the implementation of religious moderation values in realizing peaceful and inclusive education, as well as the active role of students in preventing the potential development of extremism within the campus environment. The revitalization of religious moderation values is essential not only to prevent extremist behavior but also to shape individuals who possess a holistic understanding of diversity, enabling them to contribute positively to national and civic life. This study employs a case study design with a qualitative approach. Data were collected through in-depth interviews, observations, and documentation. The findings indicate that the revitalization of religious moderation values can be carried out through various strategies, such as integrating moderation principles into the educational curriculum, strengthening character development through extracurricular activities, optimizing the use of social media, collaborating with multiple stakeholders, and conducting regular monitoring and evaluation of student activities. Furthermore, the role of lecturers in modeling exemplary behavior and reinforcing moderation narratives is highly influential in fostering a peaceful and harmonious academic atmosphere. Therefore, continuous efforts to revitalize religious moderation values within the campus environment are necessary as part of strengthening national identity grounded in the principles of Pancasila and Bhinneka Tunggal Ika.